TINJAUAN YURIDIS TERHADAP PERKAWINAN BEDA AGAMA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 - Bing Waluyo; Wiwin Muchtar Wiyono; Aris Priyadi (Collegium Studiosum Journal, 2023)
In Article 2 paragraph 1 of the Marriage Law it is stated that marriage is valid if it is carried out according to the laws of each religion and belief. In the Explanation of Article 2 paragraph 1 of the Marriage Law it is stated that no marriage is outside the law of each religion and belief in accordance with the 1945 Constitution. Thus according to law, marriage must take place according to the law of each religion and belief. If the marriage is carried out outside or contrary to the laws of each religion and belief, then the marriage is invalid. The words "the laws of each religion and its beliefs" do not mean that each party is subject to different religious laws, but that it only shows or distinguishes the religions that are adhered to by the people of Indonesia, therefore Article 2 of the Law Marriage will only be effective if the prospective husband and wife adhere to the same religion. Now the problem is if the prospective husband and wife who want to get married adhere to different religions, which party's religious law will apply to legalize the marriage, while neither party wants to give in to submit to the other party's religious law. It should be pointed out that no marriage may be legalized by two different religions at the same time, because each religion has its own principles and different marriage rules from one another, which of course have different consequences.